An Epigraphic Note on the Nabataean Text of a Bilingual (Greek-Nabataean) Inscription from Ġūr al-Ṣāfī - Petrantoni, Giuseppe (Anabasis. Studia Classica et Orientalia, 2016)
During the excavation at al-Naq‘ Byzantine cemetery (begun in 1996) of Ġūr al-Ṣāfī (Jordan), a bilingual Greek-Nabataean inscription was discovered. It was published in 2008 by Y.E. Meimaris who offers only a simple translation of the Nabataean text, in addition to the transcription and the translation of the Greek lines. The purpose of this article is to provide a transcription of the Nabataean lines in order to analyse their content and to pay specific attention to onomastics inasmuch two individuals of the inscription are differently two-named in Greek and in Nabataean. In particular, the name ’šm‘yn – Ἱσμεήλη seems to be new in the Nabataean epigraphy since it is not attested in the latter and also in other cognate varieties of Aramaic.